Synthesis and Electronic Properties of Novel Donor–π–Acceptor-Type Functional Dyes with a Carbonyl-Bridged Bithiophene π-Spacer - Miyu Ueda; Ryo Nagayama; Masaki Nagaoka; Naoya Suzuki; Shintaro Kodama; Takeshi Maeda; Shin-ichiro Kato; Shigeyuki Yagi (Molecules)
In this study, we synthesized novel donor–π–acceptor (D–π–A) functional dyes bearing a carbonyl-bridged bithiophene as a π-conjugated spacer and evaluated the absorption and fluorescence properties as well as the photostability. The developed dyes 1-CO–3-CO possess an N,N-diphenylaminophenyl electron donor unit and an electron acceptor unit such as a formyl group (1-CO), an (N,N-diethylthiobarbituryl)methylene moiety (2-CO), or a (3-dicyanomethylidene-1-indanon-2-yl)methylene moiety (3-CO). The absorption spectra of 1-CO–3-CO in dichloromethane at room temperature showed absorption maxima at 569 nm, 631 nm, and 667 nm, respectively, and the stronger acceptors in 2-CO and 3-CO led to enhancement of the ICT character. In addition, 2-CO and 3-CO had a second absorption band in the visible region, showing panchromatic absorption properties. Electrochemical analyses of the developed dyes revealed that the carbonyl bridging group in the π-spacer contributes to stabilization of the frontier orbitals such as the highest occupied and lowest unoccupied molecular orbitals (HOMO and LUMO, respectively), in comparison with the referential dyes bearing a dibutylmethylene-bridged bithiophene spacer, 1-CBu2–3-CBu2. The HOMO/LUMO stabilization brought about high photostability in the doped poly(methyl methacrylate) film.